Connecting landscape conservation and management with traditional ecological knowledge: does it matter how people perceive landscape and nature? - Carvalho, Ana Maria (2011)
Ethnobotanical surveys conducted in Trás-os-Montes highlighted a renewed interest in cultural and heritage values of landscapes. Landscape diversity is mostly based on traditional ecological knowledge (TEK) and practices that, since a long time ago, interacted with natural processes. Rural contexts face social and economical constraints and landscapes are change accordingly. This poster aims to describe recent landscape changes at a local scale and people’ perceptions. Moreover, to discuss local conceptions as important tools for landscape conservation and management